Effects of gold nanoparticles combined with human β-defensin 3 on the alveolar bone loss of periodontitis in rat - Jing Zhou (BMC, 2021)
Abstract Background Nanomaterials of biomedicine and tissue engineering have been proposed for the treatment of periodontitis in recent years. This study aimed to investigate the effects of gold nanoparticles (AuNPs) combined with human β-defensin 3 (hBD3) on the repair of the alveolar bones of experimental periodontitis in rats. Methods A model of experimental periodontitis was established by ligation of the maxillary second molars with silk thread in rats, which were treated with or without AuNPs combined with hBD3. Micro‐computerized tomography (micro-CT) scanning, enzyme-linked immunosorbent assay, and histological and immunohistochemical staining, including alkaline phosphatase (ALP), osteoprotegerin (OPG), tartrate-resistant acid phosphatase (TRAP), and receptor activator of NF-κB ligand (RANKL), were used to analyze the samples. Results Micro-CT demonstrated that the alveolar bone resorption was significantly reduced after the treatment with AuNPs combined with hBD3. Levels of TNF-α and IL-6 were decreased markedly compared with the ligation group. H&E and Masson staining showed that AuNPs combined with hBD3 group had less inflammatory cell infiltration, collagen fibrosis and fracture, but higher calcification in the new bone tissue. Moreover, the administration of AuNPs combined with hBD3 increased the expression levels of ALP and OPG (related to bone formation) while decreasing the expression levels of TRAP and RANKL (related to bone resorption) expression. Conclusions AuNPs combined with hBD3 had a protective effect on the progression of experimental periodontitis in rats and played a certain role in suppressing osteoclastogenesis and alleviating the inflammatory destruction of periodontitis along with the promotion of bone repair.